Influence of Competence, Financial Compensation and Work Discipline on Performance of Employees in Makassar Class I Navigation District - Sari, Putri; Mardjuni, Sukmawati; -, Chahyono (Indonesian Journal of Business and Management, 2018)
This study aims to test analyze and menginterpertasi; 1). the influence of competence on employee performance; 2). The effect of financial compensation on employee performance; 3).The influence of work discipline on employee performance 4). Influence of competence, financial compensation and work discipline to performance of Makassar First Class Navigation officer. The design in this research using quantitative research method dengang using survey method. The number of samples in this study were 71 people. This research used quantitative descriptive analysis technique which was analyzed with the help of SPSS 24 software. The conclusions of this study are: 1) competence has a positive and significant effect on employee performance; 2) financial compensation has a positive and significant impact on employee performance; 3). work discipline has a positive and significant impact on the performance of Makassar First Class Navigation personnel.